2000
DOI: 10.1007/s002320010004
|View full text |Cite
|
Sign up to set email alerts
|

CFTR Regulation of Intracellular Calcium in Normal and Cystic Fibrosis Human Airway Epithelia

Abstract: In cystic fibrosis airway epithelia, mutation of the CFTR protein causes a reduced response of Cl(-) secretion to secretagogues acting via cAMP. Using a Ca(2+) imaging system, the hypothesis that CFTR activation may permit ATP release and regulate [Ca(2+)](i) via a receptor-mediated mechanism, is tested in this study. Application of external nucleotides produced a significant increase in [Ca(2+)](i) in normal (16HBE14o(-) cell line and primary lung culture) and in cystic fibrosis (CFTE29o(-) cell line) human a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 50 publications
1
17
1
Order By: Relevance
“…Alternatively, the differential responses observed may be due to tissue specificity given that CF cell line tested was derived from trachea, whereas the non-CF cell line was bronchial derived. Differential responses in these two cell types have been documented in the past (41). Our finding that TLR9 is expressed on the surface of epithelial cells is in contrast to studies performed using macrophages in which TLR9 was found to be localized to endosomes and shown to become activated following internalization of uCpG DNA (42).…”
Section: Discussioncontrasting
confidence: 68%
“…Alternatively, the differential responses observed may be due to tissue specificity given that CF cell line tested was derived from trachea, whereas the non-CF cell line was bronchial derived. Differential responses in these two cell types have been documented in the past (41). Our finding that TLR9 is expressed on the surface of epithelial cells is in contrast to studies performed using macrophages in which TLR9 was found to be localized to endosomes and shown to become activated following internalization of uCpG DNA (42).…”
Section: Discussioncontrasting
confidence: 68%
“…The mechanisms by which CFTR exerts its regulatory role over other epithelial ion transporters is still incompletely understood, although several hypotheses are currently being explored. These include indirect regulation via release of ATP through CFTR with a subsequent autocrine activation of luminal purinoceptors and modulation of intracellular calcium, which in turn could regulate other transporters (8,9). Another regulatory mechanism involves direct intramembrane or cytoplasmic protein-protein interaction.…”
Section: Cystic Fibrosis Transmembrane Conductance Regulator (Cftr)mentioning
confidence: 99%
“…In addition, airway epithelial cells have also been identified as a source of extracellular ATP. Although the active release mechanisms of ATP from epithelial cells are not understood (5,7,11,36,37), epithelial trauma associated with asthma (12, 18) can result in damaged cells that passively release ATP.In many other tissues, ATP has been found to stimulate P2X and P2Y receptors, both of which have been identified in lung tissue (19,29,34,35 ] i ) of SMCs usually result in the phosphorylation of myosin light chain and the stimulation of contraction (15, 16), ATP is likely to be a potent spasmogen of airway SMCs.Surprisingly, the effects of ATP on the [Ca 2ϩ ] i of airway SMCs or on airway contraction have not been extensively studied, and the few reports that exist are inconsistent. For example, ATP was found to increase in vivo airway resistance in rats (9) or induce contraction in isolated guinea pig tracheae (8).…”
mentioning
confidence: 99%